The Design of Board Games as an ESP Teaching Experiment - Moura, Vera Lúcia de Lucena (The ESPecialist, 2012)
This paper aims at reporting a rewarding teaching experience with the design of games for the teaching of English. The games were devised by English for Special Purposes (ESP) Graphic Design students from the Federal University of Pernambuco. The paper’s goal is also to motivate colleagues to devise other ways to teach ESP. In order to accomplish this, reasons will be given for the choice of this teaching experience as well as the methodology used. A critical self-evaluation of the experiment will also be done in order to have a more accurate appraisal of the results obtained so as to be able to evaluate its success.